Analysis of the Effect of Service Quality on Customer Loyalty and Satisfaction Using Expectation Confirmation Model and Servqual - Kartika Sari; Hendri Rahmayani Asri; Hantoro Arief Gisijanto; Anggi Paramita Puti Kencana; Ibnu Cahyo Ramadhan (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2023)
he application of technology that can be used to support the buying and selling transaction system is e-commerce. The purpose of this study is to determine user perceptions of service quality and identify factors that have the greatest influence on user satisfaction and loyalty. The number of samples in this study were 315 respondents who were e-commerce users for at least one year. Sampling was carried out using purposive sampling technique. The data analysis process is carried out based on the PLS-SEM approach with SmartPLS software version 3.3.3. The model used is a combination of the ServQual model with the Expectation Confirmation Model (ECM). Overall, this study found that users' perceptions of service quality are dissatisfied with reliability and tangibels services. Of the 5 hypotheses accepted, the factors that influence satisfaction are assurance and the factors that influence customer loyalty are reliability, tangibels, assurance and satisfaction.